2003
DOI: 10.1113/jphysiol.2003.046268
|View full text |Cite
|
Sign up to set email alerts
|

Diabetes Increases Facilitative Glucose Uptake and GLUT2 Expression at the Rat Proximal Tubule Brush Border Membrane

Abstract: The mechanism of renal glucose transport involves the reabsorption of filtered glucose from the proximal tubule lumen across the brush border membrane (BBM) via a sodium‐dependent transporter, SGLT, and exit across the basolateral membrane via facilitative, GLUT‐mediated, transport. The aim of the present study was to determine the effect of streptozotocin‐induced diabetes on BBM glucose transport. We found that diabetes increased facilitative glucose transport at the BBM by 67.5 % (P < 0.05) – an effect that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
127
0
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
2
2
2

Relationship

0
6

Authors

Journals

citations
Cited by 151 publications
(143 citation statements)
references
References 35 publications
15
127
0
1
Order By: Relevance
“…Moreover, our previous study demonstrated that in STZ-induced diabetes the sodium-dependent component of renal glucose transport was unchanged, whereas the facilitative (GLUT-mediated) component was significantly enhanced. Western blotting showed an increase in both GLUT2 and GLUT5 protein at the BBM, with no change in GLUT1 protein levels; and that the upregulation of GLUT2, but not of GLUT5, could be abolished by overnight fasting [9]. Similar findings were reported by Freitas et al, who concluded that plasma glucose concentration was the key regulator of the gene encoding GLUT2 [24].…”
Section: Discussionsupporting
confidence: 83%
See 4 more Smart Citations
“…Moreover, our previous study demonstrated that in STZ-induced diabetes the sodium-dependent component of renal glucose transport was unchanged, whereas the facilitative (GLUT-mediated) component was significantly enhanced. Western blotting showed an increase in both GLUT2 and GLUT5 protein at the BBM, with no change in GLUT1 protein levels; and that the upregulation of GLUT2, but not of GLUT5, could be abolished by overnight fasting [9]. Similar findings were reported by Freitas et al, who concluded that plasma glucose concentration was the key regulator of the gene encoding GLUT2 [24].…”
Section: Discussionsupporting
confidence: 83%
“…We have reported previously that STZ-induced diabetes results in translocation of GLUT2 protein to the BBM and that this is likely to be due to hyperglycaemia [9]. The present study aimed to determine whether more modest changes in plasma glucose concentration had any effect on GLUT2 levels at the BBM.…”
Section: Resultsmentioning
confidence: 86%
See 3 more Smart Citations